PAM-AID - A study in human-machine cooperative behaviour - MacNamara, Shane (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2001)
The research described in this thesis attempts to address the needs of a growing number of people with both a visual impairment and a mobility impairment. These people tend to live a very inactive lifestyle, often confined to bed because of lack of care-givers to assist them
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin